Sea bass (Dicentrarchus labrax) as a potential bioindicator of estrogenic contamination in marine surface waters - Freitas, S. (2004)
Resumo apresentado sob poster apresentado ao 5th International Symposium on Fish Endocrinology, September, 2004, Castellon, Spain.